Pengaruh Pemanfaatan ChatGPT dalam Model Think Pair Share (TPS) terhadap Pemahaman Siswa pada Pembelajaran Pendidikan Agama Islam - Riza Roisatul Amanah; Sokhibul Arifin; Mochammad Caris Hidayat (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Agama Islam Nahdlatul Wathan Samawa Sumbawa Besar, 2026)
This study aims to examine the effect of using ChatGPT in the Think Pair Share (TPS) model on students’ understanding in Islamic Religious Education learning. This research used a quantitative approach with a quasi-experimental method and a nonequivalent control group design. The sample consisted of 60 eighth-grade students at SMP Negeri 3 Waru Sidoarjo, divided into an experimental class and a control class. Data were collected using a 20-item multiple-choice test in the form of pretest and posttest. Data analysis was conducted using descriptive statistics, normality test, homogeneity test, and independent sample t-test with SPSS version 25. The results showed that the posttest score of the experimental class was significantly higher than that of the control class. This indicates that the use of ChatGPT in the TPS model has a positive effect on students’ understanding of Islamic Religious Education, particularly on the topic of salat jamak and qashar.